Exploring the European Union Renewable Energy Directive and its Implications for Indonesias Palm Oil Industry - Bondan Widyatmoko (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2015)
The Renewable Energy Directive (RED) is a vehicle for environmental NGOs concerned about biodiversity destruction in Indonesia, for European biodiesel producers to admit new competitors, and for European Union (EU) interests to build a secure and sustainable economy for their region. In other words, it is a manifestation of the di?erent interests of many agencies that share grace and favour over palm oil development in the EU. By observing the RED as the vehicle and the EU system of governance as its course, this paper records the interactions between those agencies in shaping the policy. The observations allow for agencies contributions to the images of palm oil. It depicts that biodiversity destruction is the basis for the sustainability criteria in the RED but it was not the only cause of the slowing down in the pace of the Indonesian palm oil market penetration in the region. To some extent, the RED is considered a trade barrier for Indonesian palm oil. However, the RED is an incentive to strengthen the image of the palm oil industry in a more constructive way and ensure the longevity of the industry.